Central release of oxytocin and the ventromedial hypothalamus. (25th October 2007) - Sabatier, N.; Rowe, I.; Leng, G.
Abstract : Recent studies on the regulation of social behaviours by neuropeptides indicate that it is the distribution of peptide receptor expression in particular brain areas that determines the specificity of peptide actions; and that, accordingly, peptides can evoke specific behaviours when administered centrally without temporal or spatial selectivity of administration. The release of neuropeptides at synaptic sites appears irrelevant, and in the brain, some peptides are released mainly from dendrites rather than from nerve endings. Dendritic peptide release can be long lasting, semi-independent of electrical activity, and allows the diffusion of peptides to distant targets. The peptide oxytocin regulates many behaviours; in particular, it inhibits food intake. Centrally, oxytocin is released in large amounts by the dendrites of hypothalamic magnocellular neurons. This mini-review considers the possible involvement of dendritically released oxytocin in the regulation of food intake by its actions on the ventromedial hypothalamus.